(untitled) (Journal of Plant Disease Sciences, 2020)
Two fungicide Ridomil -MZ 72 (Metalaxyl 8%and Mancozeb 64 %) and Diathane M 45(Mancozeb 75%) which are reported to have curative properties against oomyceteswas evaluated against late blight of potato under On Farm Trial (OFT) for two consecutive years i.e 2015-16 and 2016-17 at five different location of farmer’s field in Kargil District. Ridomil –MZ 72 at 0.2% resulted in more than80 per cent disease control compare to Diathane M-45 at a rate of 0.5% where disease control over check was observed up to 62.90 per cent. Based on this result the Ridomil-MZ was further evaluated under Front Line Demonstration (FLD) and resulted 87.53% percent disease control over check and disease incidence was recorded 4.58%. Under FLD the tuber yield was increased by 65.72 % over farmer’s practice(FP) while net return and cost benefit ratio was 2.59 lacs and 1.9 respectively compare to farmer practice (control) where net return and cost benefit ratio was recorded 1.87 lacs and 0.89 respectively.